Infective Endocarditis with Multiple Mycotic Aneurysms Mimicking Vasculitis: A Case Report - Ji Hyeon Park; Hye Ryoun Jang; Jung Eun Lee; Wooseong Huh; Dae Joong Kim; Ha Young Oh; Yoon-Goo Kim (Canadian Journal of Infectious Diseases and Medical Microbiology)
The manifestation of infective endocarditis often resembles vasculitis. Approximately one in five infective endocarditis cases are referred initially to a nephrologist because of abnormal renal function or abnormal urinalysis; therefore, infection should be ruled out before diagnosing vasculitis.